2001
DOI: 10.1038/sj.gt.3301487
|View full text |Cite
|
Sign up to set email alerts
|

Efficient transduction of murine B lymphocytes and B lymphoma lines by modified adenoviral vectors: enhancement via targeting to FcR and heparan-containing proteins

Abstract: Murine lymphocytes are relatively refractory to efficient transfection or retroviral gene transduction. Adenovirus has been used as a vector to transduce a wide variety of cell types. Several advantages of adenoviruses are their ability to transduce non-cycling cells and to transduce the majority of cells in a population. Unfortunately, lymphocytes are not susceptible to infection with conventional adenovirus. Therefore, to express genes efficiently in murine B cells, we tested the ability of genetically modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 33 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…However, we were unable to generate monoclonal lineages of Pfeiffer cells expressing dCas9 and VP64. In other DLBCL cell lines, lentiviral transduction was inefficient (a known property of B lymphocytes and lymphomas [Li et al, 2001]). We therefore performed CRISPRa screens in the chronic myeloid leukemia (CML) cell line K562, which can be efficiently transduced and cloned.…”
Section: Resultsmentioning
confidence: 99%
“…However, we were unable to generate monoclonal lineages of Pfeiffer cells expressing dCas9 and VP64. In other DLBCL cell lines, lentiviral transduction was inefficient (a known property of B lymphocytes and lymphomas [Li et al, 2001]). We therefore performed CRISPRa screens in the chronic myeloid leukemia (CML) cell line K562, which can be efficiently transduced and cloned.…”
Section: Resultsmentioning
confidence: 99%
“…This problem may be overcome ex vivo by using Epstein-Barr virus vectors [22], adeno-associated virus vectors [23], or modified adenoviral vectors [24,25]. Recently, we described a transduction method accomplishing highly efficient adenoviral-mediated gene transfer in lymphoma cells [6].…”
Section: Discussionmentioning
confidence: 99%
“…One group showed that an Ad5 vector with a polylysine-containing fiber was able to transduce LPS-activated murine B cells and B cell lines (93). Another group found up to 6.5-fold enhancement of binding to B cell lines upon insertion of a CD21 binding sequence into the Ad5 fiber (94).…”
Section: Delivery Methodsmentioning
confidence: 99%